A sulfonated polyarylethersulfone water-lubricated bearing composite material and preparation method thereof
By introducing a high sulfonated polyarylether sulfone with a high degree of sulfonation into the polyarylether sulfone water lubricated bearing material, and hot pressing and sintering treatment, the problems of high friction coefficient and wear rate of the polyarylether sulfone water lubricated bearing material are solved, and a lower friction coefficient and wear rate are achieved.
Patent Information
- Application Number
- CN202411773397.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-05
AI Technical Summary
The existing polyarylethersulfone water-lubricated bearing materials have problems with high friction coefficient and high wear rate.
The sulfonated polyarylether sulfonate with high sulfonation degree was prepared by chlorosulfonation reaction, and doped into the polyarylether sulfone matrix by physical blending to ensure that the overall sulfonation degree is not more than 3%. Then, the heat press sintering treatment was carried out to form the sulfonated polyarylether sulfone water lubricated bearing composite.
By introducing sulfonate, the hydration and back electrolyte effect on the surface of the material are improved, and the effective hydration layer is formed, which reduces the friction coefficient and reduces the wear rate.
Smart Images

Figure CN119242045B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water-lubricated bearing material preparation, and in particular relates to a sulfonated polyarylethersulfone water-lubricated bearing composite material and a preparation method thereof. Background Art
[0002] The water-lubricated stern bearing is one of the important components of the ship propulsion system. During the operation of the ship, the water-lubricated bearing supports the rotation of the stern shaft and maintains the stable operation of the shaft system. Its friction coefficient and wear resistance are important parameters. Compared with the traditional oil-lubricated metal stern bearing, the water-lubricated bearing uses seawater as a lubricant, which effectively avoids the pollution of the ocean by lubricating oil. It is a green ship propulsion system component. Therefore, the research and development of new self-lubricating non-metallic materials for water-lubricated bearings is a current research hotspot. Polymer materials have the advantages of good processability, corrosion resistance, degradability and good physical properties. Therefore, the development of new polymer materials for water-lubricated bearings has become a hot research field.
[0003] Due to the inherent dipole moment of water molecules, the charged groups on the sliding interface can firmly fix the oppositely charged groups in the water molecules through electrostatic action to form a hydration layer. Therefore, through the ion-dipole effect, the friction between the two friction pairs is converted into the friction of the two surface water molecules. The hydration layer has high stability and a large load-bearing capacity. The water molecules in the hydration layer can quickly exchange with free water molecules, have good relaxation efficiency, and have a good fluid effect and friction coefficient in the face of shear force. Based on this theory, the research center of water-lubricated materials is to introduce polar charged functional groups into the base material to improve the hydration effect.
[0004] Polyarylethersulfone is one of the special engineering plastics. The structural unit is an electron-rich diphenol derivative and an electron-poor phenylsulfone derivative. Polyarylethersulfone has the advantages of high temperature resistance, hydrolysis resistance, excellent creep resistance and high mechanical strength, which meets the material selection requirements of water-lubricated bearing materials. Compared with special engineering plastics such as polyetheretherketone and polyimide, polyarylethersulfone is cheap, but has problems such as high friction coefficient and high wear rate. At present, the research is mainly to improve its friction performance by filling reinforcing agents such as fibers or lubricants such as graphite and molybdenum disulfide. In the field of mechanical engineering, due to the compatibility between fillers and the matrix, the friction performance of polyarylethersulfone is limited, which is subject to certain restrictions in the application and development of water-lubricated bearings under harsh working conditions.
[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a sulfonated polyarylethersulfone water-lubricated bearing composite material and a preparation method thereof, aiming to solve the problems of high friction coefficient and high wear rate of the existing polyarylethersulfone water-lubricated bearing materials.
[0007] The technical solution of the present invention is as follows:
[0008] A method for preparing a sulfonated polyarylethersulfone water-lubricated bearing composite material, comprising the steps of:
[0009] dissolving polyarylethersulfone and trimethylsilyl chloride in a dichloromethane solution to obtain a mixed solution;
[0010] Dissolving chlorosulfonic acid in a dichloromethane solution to obtain a chlorosulfonic acid solution;
[0011] The chlorosulfonic acid solution is added dropwise to the mixed solution, and after the reaction is completed, the reaction solution is poured into an ethanol aqueous solution to precipitate a white solid;
[0012] The white solid is crushed into particles, placed in an inorganic strong base solution and stirred overnight, and filtered and dried to obtain sulfonated polyarylethersulfone powder;
[0013] The sulfonated polyarylethersulfone powder and the polyarylethersulfone matrix are mixed in a ratio of an overall sulfonation degree not greater than 3%, wherein the overall sulfonation degree is calculated as follows: overall sulfonation degree = sulfonation degree of sulfonated polyarylethersulfone powder × mass of sulfonated polyarylethersulfone powder / (mass of sulfonated polyarylethersulfone powder + mass of polyarylethersulfone matrix); the mixture is then transferred to a mold for hot pressing and sintering treatment, and finally demolding and polishing are performed to obtain a sulfonated polyarylethersulfone water-lubricated bearing composite material.
[0014] The preparation method of the sulfonated polyarylethersulfone water-lubricated bearing composite material comprises the steps of adding the chlorosulfonic acid solution dropwise to the mixed solution, pouring the reaction solution into an ethanol aqueous solution after the reaction is completed to precipitate a white solid, the reaction temperature is 25-35°C, and the reaction time is 12-24h.
[0015] The method for preparing the sulfonated polyarylethersulfone water-lubricated bearing composite material comprises the following steps: in the step of adding the chlorosulfonic acid solution dropwise to the mixed solution, the ratio of the volume of chlorosulfonic acid in the chlorosulfonic acid solution to the mass of the polyarylethersulfone in the mixed solution is: 1.5-2.0 mL: 10-15 g.
[0016] In the method for preparing the sulfonated polyarylethersulfone water-lubricated bearing composite material, the inorganic strong alkali solution is one or both of a sodium hydroxide solution and a potassium hydroxide solution.
[0017] The preparation method of the sulfonated polyarylethersulfone water-lubricated bearing composite material comprises the following steps: mixing the sulfonated polyarylethersulfone powder and the polyarylethersulfone matrix in a ratio of an overall sulfonation degree not greater than 3%, and then transferring the mixture into a mold for hot pressing and sintering treatment, wherein the temperature is raised from room temperature to 280-300°C within 1-3 hours and kept warm for 0.5-1 hour; and the pressure is set to 10-20MPa.
[0018] The method for preparing the sulfonated polyarylethersulfone water-lubricated bearing composite material, wherein the step of mixing the sulfonated polyarylethersulfone powder and the polyarylethersulfone matrix in a ratio of an overall sulfonation degree of no more than 3% comprises:
[0019] 97.5 parts of polyarylethersulfone powder and 2.5 parts of the sulfonated polyarylethersulfone powder were mixed by weight, wherein the sulfonation degree of the sulfonated polyarylethersulfone powder was 40%.
[0020] The method for preparing the sulfonated polyarylethersulfone water-lubricated bearing composite material, wherein the step of mixing the sulfonated polyarylethersulfone powder and the polyarylethersulfone matrix in a ratio of an overall sulfonation degree of no more than 3% comprises:
[0021] 92.5 parts of polyarylethersulfone powder and 7.5 parts of sulfonated polyarylethersulfone powder were mixed by weight, wherein the sulfonation degree of the sulfonated polyarylethersulfone powder was 40%.
[0022] The method for preparing the sulfonated polyarylethersulfone water-lubricated bearing composite material, wherein the step of mixing the sulfonated polyarylethersulfone powder and the polyarylethersulfone matrix in a ratio of an overall sulfonation degree of no more than 3% comprises:
[0023] 83.3 parts of polyarylethersulfone powder, 6.7 parts of the sulfonated polyarylethersulfone powder, and 10 parts of carbon fiber were mixed by weight, wherein the sulfonation degree of the sulfonated polyarylethersulfone powder was 40%.
[0024] A sulfonated polyarylethersulfone water-lubricated bearing composite material is prepared by the preparation method of the sulfonated polyarylethersulfone water-lubricated bearing composite material of the present invention.
[0025] Beneficial effects: The present invention provides a method for preparing a sulfonated polyarylethersulfone water-lubricated bearing composite material. Based on the hydration lubrication mechanism, a sulfonated polyarylethersulfone with a high degree of sulfonation is first prepared by a chlorosulfonation reaction, and then the sulfonated polyarylethersulfone is doped into a polyarylethersulfone matrix by physical blending to introduce sulfonate groups into the matrix; under water lubrication, the strong hydration and counter-electrolyte effect of the negatively charged functional groups are utilized to enable the modified sulfonated polyarylethersulfone surface to quickly form an effective hydration layer to reduce the friction coefficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The present invention is a flow chart of a method for preparing a sulfonated polyarylethersulfone water-lubricated bearing composite material.
[0027] Figure 2 The schematic diagram of the chemical synthesis for preparing sulfonated polyarylethersulfone of the present invention is shown in FIG.
[0028] Figure 3This is the hydrogen nuclear magnetic resonance spectrum of the sulfonated polyarylethersulfone in Example 1 of the present invention.
[0029] Figure 4 The figure is a comparison chart of the gel permeation chromatography retention times of the sulfonated polyarylethersulfone and polyarylethersulfone of the present invention.
[0030] Figure 5 This is a comparison chart of friction coefficient curves of water-lubricated bearing materials prepared in Examples 1-3 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION
[0031] The present invention provides a sulfonated polyarylethersulfone water-lubricated bearing composite material and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0032] The terms "first", "second", "third", "fourth", etc. (if any) in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments described herein can be implemented in an order other than that illustrated or described herein. In addition, the terms "including" or "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0033] For ease of understanding, the specific process of the embodiment of the present invention is described below. Figure 1 The first embodiment of the method for preparing the sulfonated polyarylethersulfone water-lubricated bearing composite material in the embodiment of the present invention comprises:
[0034] S10, dissolving polyarylethersulfone and trimethylsilyl chloride in a dichloromethane solution to obtain a mixed solution;
[0035] S20, dissolving chlorosulfonic acid in a dichloromethane solution to obtain a chlorosulfonic acid solution;
[0036] S30, adding the chlorosulfonic acid solution dropwise to the mixed solution, and after the reaction is completed, pouring the reaction solution into an ethanol aqueous solution to precipitate a white solid;
[0037] S40, crushing the white solid into particles, placing the particles in an inorganic strong base solution and stirring overnight, filtering and drying to obtain a sulfonated polyarylethersulfone powder;
[0038] S50, mixing the sulfonated polyarylethersulfone powder and the polyarylethersulfone matrix in a ratio of an overall sulfonation degree not greater than 3%, wherein the overall sulfonation degree is calculated as follows: overall sulfonation degree = sulfonation degree of sulfonated polyarylethersulfone powder × mass of sulfonated polyarylethersulfone powder / (mass of sulfonated polyarylethersulfone powder + mass of polyarylethersulfone matrix); then transferring the mixture to a mold for hot pressing and sintering treatment, and finally demolding and polishing to obtain the sulfonated polyarylethersulfone water-lubricated bearing composite material.
[0039] Specifically, first, poly(aryl ether sulfone) and trimethylsilyl chloride are dissolved in dichloromethane. This step is to make the poly(aryl ether sulfone) dispersed in the solvent better. At the same time, trimethylsilyl chloride protects certain groups of the poly(aryl ether sulfone) by silylation. Then, chlorosulfonic acid is dissolved in dichloromethane and slowly added to the reaction system through a dropping funnel. In this process, Figure 2 As shown, chlorosulfonic acid is used as a sulfonating agent here. The chlorosulfonic acid (HSO3Cl) first reacts with trimethylsilyl chloride (TMSCl) to generate sulfonated trimethylsilane (TMS-SO3Cl), and the generated TMS-SO3Cl is then reacted with polyarylethersulfone. Substitution reaction occurs to generate After the reaction is completed, the reaction solution is poured into an ethanol aqueous solution to precipitate a white solid. This step utilizes the low solubility of the sulfonic acid group in the ethanol aqueous solution to precipitate the sulfonated product. Finally, the white solid is broken into small particles and placed in an inorganic strong base solution (for example, NaOH solution) and stirred overnight. The Na + Substitute trimethylsilane to generate sulfonated polyarylethersulfone powder The NaOH solution is also used to remove unreacted chlorosulfonic acid and other impurities.
[0040] In this embodiment, sulfonated polyarylethersulfone powders with different degrees of sulfonation can be obtained by adjusting the amount of polyarylethersulfone and chlorosulfonic acid. As an example, under a nitrogen atmosphere, 10-15 g of polyarylethersulfone and 3-4 mL of trimethylsilyl chloride are dissolved in 100-150 mL of dichloromethane solution to obtain a mixed solution; 1.5 mL-2.0 mL of chlorosulfonic acid is dissolved in 20 mL of dichloromethane, added to 100 mL of the mixed solution, and reacted at 25-35°C for 24 hours; after the reaction, the reaction solution is poured into an ethanol aqueous solution to precipitate a white solid, which is broken into small particles, placed in a NaOH solution and stirred overnight, and filtered and dried to obtain a sulfonated polyarylethersulfone powder. In this embodiment, by controlling the volume mass ratio of chlorosulfonic acid to polyarylethersulfone to 1.5-2.0 mL: 10-15 g, a sulfonated polyarylethersulfone powder with a sulfonation degree of 40% can be obtained.
[0041] In this embodiment, after obtaining a sulfonated polyarylethersulfone with a high degree of sulfonation by chlorosulfonation reaction, the sulfonated polyarylethersulfone is doped into the polyarylethersulfone matrix by physical blending, thereby introducing a certain amount of sulfonate groups into the polyarylethersulfone matrix. Due to the small entanglement force between polymer molecular chains with high molecular structure symmetry, during the sliding friction process, the flexible high molecular polymer containing linear molecular segments exhibits lower shear strength than the nonlinear and rigid high molecular polymer containing macromolecular side groups, and shear sliding easily occurs, thereby exhibiting a low friction coefficient. However, the present embodiment found through experiments that the introduction of excessive sulfonate groups during the molding process of the sulfonated polyarylethersulfone water-lubricated bearing composite material will affect the entanglement of the molecular chains and thus affect the friction performance of the material. Therefore, the present embodiment needs to ensure that the overall sulfonation degree is not greater than 3% during the process of doping the sulfonated polyarylethersulfone powder; the sulfonated polyarylethersulfone water-lubricated bearing composite material obtained under this condition is a flexible high molecular polymer of linear molecular segments, which can realize the strong hydration and counter electrolyte effect of the negatively charged functional groups under water lubrication, so that the modified sulfonated polyarylethersulfone surface quickly forms an effective hydration layer to reduce the friction coefficient.
[0042] In some embodiments, the inorganic strong alkali solution is one or both of a sodium hydroxide solution and a potassium hydroxide solution, but is not limited thereto.
[0043] In some embodiments, the sulfonated polyarylethersulfone powder and the polyarylethersulfone matrix are mixed in a ratio of not more than 3% of the overall sulfonation degree, and then transferred to a mold for hot pressing sintering treatment, the temperature is raised from room temperature to 280-300°C within 1-3 hours, and the temperature is kept for 0.5-1 hour; the pressure is set to 10-20MPa. Under this condition, the sulfonated polyarylethersulfone powder and the polyarylethersulfone matrix can be effectively entangled, thereby ensuring the sulfonated polyarylethersulfone water-lubricated bearing composite material has better friction performance.
[0044] In some embodiments, 97.5 parts of polyarylethersulfone powder and 2.5 parts of the sulfonated polyarylethersulfone powder are mixed by weight, and the sulfonation degree of the sulfonated polyarylethersulfone powder is 40%. The overall sulfonation degree of the sulfonated polyarylethersulfone water-lubricated bearing composite material prepared under the conditions of this embodiment is 1%. At this time, the introduction of sulfonate groups will not affect the entanglement of molecular chains, and the sulfonated polyarylethersulfone water-lubricated bearing composite material prepared in this embodiment can realize the strong hydration and counter electrolyte effect of the negatively charged functional groups under water lubrication, so that the modified sulfonated polyarylethersulfone surface quickly forms an effective hydration layer to reduce the friction coefficient.
[0045] In some embodiments, 92.5 parts of polyarylethersulfone powder and 7.5 parts of the sulfonated polyarylethersulfone powder are mixed by weight, and the sulfonation degree of the sulfonated polyarylethersulfone powder is 40%. The overall sulfonation degree of the sulfonated polyarylethersulfone water-lubricated bearing composite material prepared under the conditions of this embodiment is 3%. At this time, the introduction of sulfonate groups will not affect the entanglement of molecular chains, and the sulfonated polyarylethersulfone water-lubricated bearing composite material prepared in this embodiment can realize the strong hydration and counter electrolyte effect of the negatively charged functional groups under water lubrication, so that the modified sulfonated polyarylethersulfone surface quickly forms an effective hydration layer to reduce the friction coefficient.
[0046] In some embodiments, 83.3 parts of polyarylethersulfone powder, 6.7 parts of the sulfonated polyarylethersulfone powder, and 10 parts of carbon fiber are mixed by weight, and the sulfonation degree of the sulfonated polyarylethersulfone powder is 40%. The overall sulfonation degree of the sulfonated polyarylethersulfone water-lubricated bearing composite material prepared under the conditions of this embodiment is 2.98%. At this time, the introduction of sulfonate groups will not affect the entanglement of molecular chains. The sulfonated polyarylethersulfone water-lubricated bearing composite material prepared in this embodiment can realize the strong hydration and counter electrolyte effect of the negatively charged functional groups under water lubrication, so that the modified sulfonated polyarylethersulfone surface quickly forms an effective hydration layer to reduce the friction coefficient; and the carbon fiber provides a supporting role as a resin reinforcing agent, which can further improve the tribological properties of the material.
[0047] The present invention will be further explained below by means of specific embodiments:
[0048] Example 1
[0049] A method for preparing a sulfonated polyarylethersulfone water-lubricated bearing composite material comprises the following steps:
[0050] Under nitrogen atmosphere, 10-15g polyarylethersulfone and 3-4mL trimethylsilyl chloride are dissolved in 100-150mL dichloromethane solution to obtain a mixed solution. 1.5-2.0mL chlorosulfonic acid is dissolved in 20mL dichloromethane, added to 100mL mixed solution, and reacted at 25-35°C for 24 hours; after the reaction, the reaction solution is poured into ethanol aqueous solution to precipitate white solid, which is broken into small particles, placed in NaOH solution and stirred overnight, filtered and dried to obtain sulfonated polyarylethersulfone powder with a sulfonation degree of 40%;
[0051] 97.5 parts of polyarylethersulfone powder and 2.5 parts of sulfonated polyarylethersulfone powder are fully mixed in a high-speed mixer at 1000-2000r / min, and then transferred to a cylindrical mold with a diameter of 30 mm for hot pressing and sintering. The room temperature is raised to 280-300°C in 1-3 hours and kept warm for 0.5-1 hour; then the temperature is lowered to room temperature at a rate of 1-5°C / min, the pressure of hot pressing is set to 10-20MPa, and the mold is demolded after cooling to 30-50°C. After polishing, the sulfonated polyarylethersulfone water-lubricated bearing composite material is obtained.
[0052] Example 2
[0053] A method for preparing a sulfonated polyarylethersulfone water-lubricated bearing composite material comprises the following steps:
[0054] Under nitrogen atmosphere, 10-15g polyarylethersulfone and 3-4mL trimethylsilyl chloride are dissolved in 100-150mL dichloromethane solution to obtain a mixed solution. 1.5-2.0mL chlorosulfonic acid is dissolved in 20mL dichloromethane, added to 100mL mixed solution, and reacted at 25-35°C for 24 hours; after the reaction, the reaction solution is poured into ethanol aqueous solution to precipitate white solid, which is broken into small particles, placed in NaOH solution and stirred overnight, filtered and dried to obtain sulfonated polyarylethersulfone powder with a sulfonation degree of 40%;
[0055] 92.5 parts of polyarylethersulfone powder and 7.5 parts of sulfonated polyarylethersulfone powder are fully mixed in a high-speed mixer at 1000-2000r / min, and then transferred to a cylindrical mold with a diameter of 30mm for hot pressing and sintering. The room temperature is raised to 280-300℃ in 1-3 hours and kept warm for 0.5-1 hour; then the temperature is lowered to room temperature at a rate of 1-5℃ / min, the pressure of hot pressing is set to 10-20MPa, and the mold is demolded after cooling to 30-50℃, and the sulfonated polyarylethersulfone water-lubricated bearing composite material is obtained after polishing.
[0056] Example 3
[0057] A method for preparing a sulfonated polyarylethersulfone water-lubricated bearing composite material comprises the following steps:
[0058] Under nitrogen atmosphere, 10-15g polyarylethersulfone and 3-4mL trimethylsilyl chloride are dissolved in 100-150mL dichloromethane solution to obtain a mixed solution. 1.5-2.0mL chlorosulfonic acid is dissolved in 20mL dichloromethane, added to 100mL mixed solution, and reacted at 25-35°C for 24 hours; after the reaction, the reaction solution is poured into ethanol aqueous solution to precipitate white solid, which is broken into small particles, placed in NaOH solution and stirred overnight, filtered and dried to obtain sulfonated polyarylethersulfone powder with a sulfonation degree of 40%;
[0059] 83.3 parts of polyarylethersulfone powder, 6.7 parts of sulfonated polyarylethersulfone powder and 10 parts of carbon fiber are fully mixed in a high-speed mixer at 1000-2000r / min, and then transferred to a cylindrical mold with a diameter of 30mm for hot pressing and sintering. The room temperature is raised to 280-300℃ in 1-3 hours and kept warm for 0.5-1 hour; then the temperature is lowered to room temperature at a rate of 1-5℃ / min, the pressure of hot pressing is set to 10-20MPa, and the mold is demolded after cooling to 30-50℃, and the sulfonated polyarylethersulfone water-lubricated bearing composite material is obtained after polishing.
[0060] Comparative Example 1
[0061] A method for preparing a polyarylethersulfone water-lubricated bearing material comprises the following steps:
[0062] 100 portions of polyarylethersulfone powder were transferred to a cylindrical mold with a diameter of 30 mm for hot pressing and sintering. The room temperature was raised to 280-300°C in 1-3 hours and kept warm for 0.5-1 hour. The temperature was lowered to room temperature at a rate of 1-5°C / min. The hot pressing pressure was set to 10-20 MPa. After cooling to 30-50°C, demolding was performed and the polyarylethersulfone water-lubricated bearing material was obtained after polishing.
[0063] Comparative Example 2
[0064] A method for preparing a sulfonated polyarylethersulfone water-lubricated bearing composite material comprises the following steps:
[0065] Under nitrogen atmosphere, 10-15g polyarylethersulfone and 3-4mL trimethylsilyl chloride are dissolved in 100-150mL dichloromethane solution to obtain a mixed solution. 1.5-2.0mL chlorosulfonic acid is dissolved in 20mL dichloromethane, added to 100mL mixed solution, and reacted at 25-35°C for 24 hours; after the reaction, the reaction solution is poured into ethanol aqueous solution to precipitate white solid, which is broken into small particles, placed in NaOH solution and stirred overnight, filtered and dried to obtain sulfonated polyarylethersulfone powder with a sulfonation degree of 40%;
[0066] 87.5 parts of polyarylethersulfone powder and 12.5 parts of sulfonated polyarylethersulfone powder are fully mixed in a high-speed mixer at 1000-2000r / min, and then transferred to a cylindrical mold with a diameter of 30mm for hot pressing and sintering. The room temperature is raised to 280-300℃ in 1-3 hours and kept warm for 0.5-1 hour; then the temperature is lowered to room temperature at a rate of 1-5℃ / min, the pressure of hot pressing is set to 10-20MPa, and the mold is demolded after cooling to 30-50℃, and the sulfonated polyarylethersulfone water-lubricated bearing composite material is obtained after polishing.
[0067] Test Example 1
[0068] Using deuterated dimethyl sulfoxide as a deuterated reagent, the sulfonated polyarylethersulfone powder prepared in Example 1 was subjected to nuclear magnetic resonance, and the following Figure 3 As shown in the resonance hydrogen spectrum, it can be seen from the figure that the integral of the chemical shift at 7.72 is 0.4, indicating that the sulfonation degree of the prepared sulfonated polyarylethersulfone is 40%; the sulfonated polyarylethersulfone powder prepared in Example 1 and the unmodified polyarylethersulfone are further subjected to gel permeation treatment to obtain Figure 4 As shown in the gel permeation chromatogram, it can be seen that the retention time of the sulfonated poly(arylethersulfone) with a sulfonation degree of 40% is basically consistent with that of the unmodified poly(arylethersulfone), indicating that the molecular chain of the poly(arylethersulfone) is not broken during the sulfonation process and is still a high molecular polymer with linear molecular segments.
[0069] Test Example 2
[0070] The bearing materials in Examples 1-3 and Comparative Examples 1-2 were tested using a UMT rotary friction and wear tester. The friction pair was a silicon nitride ball with a diameter of 10 mm, the rotation speed was 100 rpm, the linear velocity was 0.05 m / s, the load weight was 15 N, and a 3% NaCl solution was selected as the test environment. The experimental results are as follows: Figure 5 As shown in Table 1. Figure 5 As can be seen from Table 1, the test time is 1 hour, the friction coefficient of the unmodified polyarylethersulfone (Comparative Example 1) is 0.070, and the friction coefficient of the polyarylethersulfone doped with a certain amount of sulfonated polyarylethersulfone (Example 1 and Example 2) is reduced to 0.059 and 0.040 respectively. This is because the introduction of sulfonate groups improves the hydration of the surface of the polyarylethersulfone material, forms a hydration layer between the friction pairs, and achieves a hydration lubrication effect, thereby reducing the friction coefficient; however, the friction coefficient of the polyarylethersulfone doped with excessive sulfonated polyarylethersulfone (Comparative Example 2) is 0.077, which is higher than that of pure polyarylethersulfone. This is because the introduction of excessive sulfonate groups during the molding process affects the entanglement of molecular chains, thereby affecting the friction properties of the material; compared with Example 2, the friction coefficient of the sample doped with carbon fiber in Example 3 is further reduced, because the synergistic effect of the support effect and the hydration lubrication effect of the carbon fiber improves the friction properties of the material.
[0071] Table 1 Friction coefficient, wear rate and contact angle test results
[0072]
[0073] The wear rate of the bearing materials in Examples 1-3 and Comparative Examples 1-2 was measured by white light diffractometer, and the results are shown in Table 1. It can be seen from Table 1 that the wear rate of the unmodified polyarylethersulfone (Comparative Example 1) is 6.77× 10-7 mm3 / (NM), and the wear rate is reduced after a certain amount of sulfonated polyarylethersulfone (Example 1 and Example 2) is doped, which are 5.19× 10-7 mm3 / (NM) and 4.16× 10-7 mm3 / (NM), respectively; however, the wear rate of the excessively doped sulfonated polyarylethersulfone (Comparative Example 2) increases significantly, and the wear rate of the composite material doped with carbon fiber in Example 3 further decreases to 2.76× 10-7 mm3 / (NM).
[0074] The hydrophilicity of the bearing material surface in Examples 1-3 and Comparative Examples 1-2 was measured using a contact angle meter. From Table 1, it can be seen that the surface contact angle of pure polyarylethersulfone (Comparative Example 1) is 82.3, and the surface contact angle decreases after the addition of sulfonated polyarylethersulfone. Compared with Example 2, the contact angle of Example 3 increases slightly after the addition of carbon fiber.
[0075] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a sulfonated polyarylethersulfone water-lubricated bearing composite material, characterized in that: Includes steps: Under a nitrogen atmosphere, 10-15 g of poly(arylethersulfone) and 3-4 mL of trimethylsilyl chloride are dissolved in 100-150 mL of dichloromethane solution to obtain a mixed solution; Dissolve 1.5 mL-2.0 mL of chlorosulfonic acid in 20 mL of dichloromethane to obtain a chlorosulfonic acid solution, add the solution to 100 mL of the mixed solution, react at 25-35° C. for 24 hours, pour the reaction solution into an ethanol aqueous solution after the reaction to precipitate a white solid, break it into small particles, place it in a NaOH solution and stir overnight, filter and dry it to obtain a sulfonated polyarylethersulfone powder, wherein the sulfonation degree of the sulfonated polyarylethersulfone powder is 40%, and the NaOH solution is also used to remove unreacted chlorosulfonic acid and other impurities, wherein the volume of chlorosulfonic acid in the chlorosulfonic acid solution and the mass ratio of the polyarylethersulfone in the mixed solution is 1.5-2.0 mL: 10-15 g; The sulfonated polyarylethersulfone powder and the polyarylethersulfone matrix are mixed in a ratio of an overall sulfonation degree not greater than 3%, wherein the overall sulfonation degree is calculated as follows: overall sulfonation degree = sulfonation degree of sulfonated polyarylethersulfone powder × mass of sulfonated polyarylethersulfone powder / (mass of sulfonated polyarylethersulfone powder + mass of polyarylethersulfone matrix), and then transferred to a mold for hot pressing and sintering treatment, wherein the hot pressing and sintering treatment step is to increase the temperature from room temperature to 280-300°C within 1-3h, and keep the temperature for 0.5-1h, the pressure is set to 10-20MPa, and finally demolding and polishing are performed to obtain the sulfonated polyarylethersulfone water-lubricated bearing composite material.
2. The method for preparing the sulfonated polyarylethersulfone water-lubricated bearing composite material according to claim 1, characterized in that: The step of mixing the sulfonated polyarylethersulfone powder and the polyarylethersulfone matrix in a ratio of an overall sulfonation degree of no more than 3% comprises: 97.5 parts of polyarylethersulfone powder and 2.5 parts of the sulfonated polyarylethersulfone powder were mixed by weight.
3. The method for preparing the sulfonated polyarylethersulfone water-lubricated bearing composite material according to claim 1, characterized in that: The step of mixing the sulfonated polyarylethersulfone powder and the polyarylethersulfone matrix in a ratio of an overall sulfonation degree of no more than 3% comprises: 92.5 parts of polyarylethersulfone powder and 7.5 parts of sulfonated polyarylethersulfone powder were mixed by weight, wherein the sulfonation degree of the sulfonated polyarylethersulfone powder was 40%.
4. The method for preparing the sulfonated polyarylethersulfone water-lubricated bearing composite material according to claim 1, characterized in that: The step of mixing the sulfonated polyarylethersulfone powder and the polyarylethersulfone matrix in a ratio of an overall sulfonation degree of no more than 3% comprises: 83.3 parts of polyarylethersulfone powder, 6.7 parts of the sulfonated polyarylethersulfone powder, and 10 parts of carbon fiber were mixed by weight, wherein the sulfonation degree of the sulfonated polyarylethersulfone powder was 40%.
5. A sulfonated polyarylethersulfone water-lubricated bearing composite material, characterized in that: The composite material is prepared by the method for preparing the sulfonated polyarylethersulfone water-lubricated bearing composite material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Polyether sulfone composite material and preparation method and application thereof
CN105255189A
Sulfonated polyether-ether-ketone resin, water-lubricated bearing composite material and preparation method thereof
CN118546353A
Method for manufacture of sulfonated polysulfone-based polymer
KR102056689B1